ESTUDO COMPARATIVO DA EFICIÊNCIA E EFICÁCIA DE DIFERENTES INSTRUMENTOS PARA REMOÇÃO DE PINOS DE FIBRA COMPARATIVE STUDY OF THE EFFICIENCY AND EFFECTIVENESS OF DIFFERENT INSTRUMENTS FOR FIBER POST REMOVAL - Bragatto, Giuliano; Crusoé-Rebello, Ieda Margarida; Neves, Frederico Sampaio; Mendes, Christtson Cesar; Oliveira, Viviane Maia Barreto de (Revista da Faculdade de Odontologia da Universidade Federal da Bahia, 2020)
Objective: The aim of this study was to evaluate the efficiency and effectiveness of different instruments to remove fiber post (FP): long spherical diamond tip 1012 (KG Sorensen) (LSDT); ultrasonic insert with spherical diamond post, model TRI27DP-A32 (Trinks); and E5 long conical ultrasonic insert (Helse).Materials and Methods: this randomized in vitrostudy used 30 inferior bovine primary incisors roots,endodontically treated, subdivided into 3 groups. A fiberglass post model DCE 0.5 (FGM) was cemented in each root and removed. The following were evaluated: removal times; the pre and post weights removal of the fiberglass post; and the area change of the conduit after removal of the FP. Results: The three groups obtained times of removal the FP statistically different from each other. The LSDT obtained the shortest time, followed respectively by the diamond spherical post and the long conical insert. Regarding the weight variation, only in the group of the spherical diamond postinsert did not present a statistically significant change. The data referring to the change in the total area revealed that the LSDT and the diamond spherical post insert did not show statistically significant changes, with a significance level of 5%. However, the individualized evaluation of the root thirds showed that, in the apical and middle thirds, only the spherical diamond post tip did not promote statistically significant alterations, and in the cervical third only the LSDT did not promote statistically significant alterations. Conclusions: The LSDT was efficient but not effective; the diamond- -shaped spherical post was effective, but not efficient; and the E5 long conical ultrasound insert was neither efficient nor effective; suggesting that the association of the LSDT in the cervical third, and the insertion for ultrasound pulls spherical diamond post in the middle and apical thirds is the best option.